2017
DOI: 10.1177/1933719117702013
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen Activator Inhibitor-1 Polymorphism Confers a Genetic Contribution to the Risk of Recurrent Spontaneous Abortion: An Updated Meta-Analysis

Abstract: Various studies have investigated the risk of recurrent spontaneous abortion (RSA) with plasminogen activator inhibitor-1 ( PAI-1) 4G/5G polymorphism. However, the results have been somewhat contradictory. Therefore, an updated meta-analysis based on 31 studies (5617 cases and 3952 controls) was undertaken to clarify this relationship. The degree of RSA risk was estimated using the odds ratio (OR) and the 95% confidence interval (CI). Overall, the random effects OR was 1.464 (95% CI: 1.269-1.690) for 4G versus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Another meta-analysis, was made by [9], they used new and more rigorous inclusion criteria: 1-evaluate the association between PAI-1 4G/5G with the risk of recurrent abortion, 2-studies case-control, our projected with cohort 3-Studies with enough information to infer results. This analysis showed that there is an association of PAI-1 4G/5G with recurrent abortion in Caucasians, Asians and Africans, but not in Latinos.…”
Section: Resultsmentioning
confidence: 99%
“…Another meta-analysis, was made by [9], they used new and more rigorous inclusion criteria: 1-evaluate the association between PAI-1 4G/5G with the risk of recurrent abortion, 2-studies case-control, our projected with cohort 3-Studies with enough information to infer results. This analysis showed that there is an association of PAI-1 4G/5G with recurrent abortion in Caucasians, Asians and Africans, but not in Latinos.…”
Section: Resultsmentioning
confidence: 99%
“…96 Similarly, meta-analyses investigating the association between PAI-1 4G/5G polymorphism and recurrent pregnancy loss found a significant association between 4G/4G genotype and recurrent pregnancy loss. 97 98 99 However, Su et al reported no association between recurrent pregnancy loss and PAI-1 4G/4G genotype. 100 Thus, the conflicting results found in this paper are also reflected in contradictory results of previous published meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-analyses have investigated the association between the PAI-1 4G/5G polymorphism and adverse pregnancy outcomes. 96 97 98 99 100 Zhao et al reported significantly higher risk of preeclampsia in women carrying the 4G/4G genotype. 96 Similarly, meta-analyses investigating the association between PAI-1 4G/5G polymorphism and recurrent pregnancy loss found a significant association between 4G/4G genotype and recurrent pregnancy loss.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of RPL is complicated, and several risk factors are involved in the development of the disease. In addition to fetal and maternal factors, including chromosomal abnormalities, endocrine and metabolic aberrations, and autoimmune abnormalities, genetic single nucleotide polymorphisms at different loci, also play essential roles in RPL ( 6 , 12 , 39 ) . In this meta-analysis, we evaluated the association of the ACE I/D and PAI-1 4G/5G polymorphisms with RPL risk in Iranian women from all eligible case-control studies.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombotic disorders are detectable in 40-50% of RPL cases ( 11 ) . It has been presumed that the etiology of RPL is associated with factors involved in fibrinolysis and coagulation ( 3 , 12 ) . In the past two decades, several investigators suggested that thrombophilia had an impact on susceptibility to RPL ( 13 , 14 , 15 ) .…”
Section: Introductionmentioning
confidence: 99%